ANALISIS PERSEPSI PENGUNJUNG TERHADAP KENYAMANAN RUANG TERBUKA HIJAU (RTH) TONJENG BERU KELURAHAN PRAPEN KECAMATAN PRAYA - Widiawati, Baiq; Ichsan, Andi Chairil; Lestari, Andi Tri (Universitas Tanjungpura, 2024)
Based on Law Number 26 of 2007 concerning spatial planning, what is meant by Green Open Space (RTH) is an elongated area, path or group whose users are more open, where plants grow, both those that grow naturally and those that are deliberately planted. This research aims to analyze visitors